Manajemen Keuangan dalam Usaha Kecil dan Menengah: Perspektif Economic Growth dan Economic of Scale - Bustanul Ulum; Mochamad Syafii; Adiba Fuad Syamlan (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to explore financial management practices in small and medium enterprises (SMEs) and understand the meaning, experiences, and strategies used by entrepreneurs in managing finances. This study uses a qualitative approach with a phenomenological design to explore the subjective experiences of SME entrepreneurs. Data sources were collected through several stages of data collection from SME entrepreneurs selected using purposive and snowball sampling techniques. The results reveal several key themes, namely limited understanding of financial management, mixing personal and business finances, the influence of social and cultural factors, experience-based adaptive strategies, and the low utilization of digital technology in financial management. These findings indicate that SME financial practices are not only influenced by technical factors but also by social, cultural, and psychological aspects